Tanggung Jawab Komisaris atas Perbuatan Melanggar Hukum Ditinjau dari Doktrin Piercing The Corporate Veil - Nathasya, Jessica Putry; Sudarwanto, Albertus Sentot (Indonesian Publication Center, 2026)
This study analyzes the regulation of company organs’ responsibilities, particularly commissioners, under Law Number 40 of 2007 concerning Limited Liability Companies and its relevance to the doctrine of piercing the corporate veil. The case of PT WSM Ventures Indonesia is examined to assess the limits of commissioners’ authority, the nature of the unlawful acts committed, and the legal basis for imposing personal liability for corporate losses. This research is a normative juridical study employing statutory and case approaches. It relies on primary and secondary legal materials obtained through literature review and applies a prescriptive analytical method. The findings show that the Company Law grants commissioners limited liability protection insofar as they perform their supervisory and advisory functions in good faith and within the scope of their authority. However, when a commissioner exceeds such authority (ultra vires) and interferes in the company’s management, causing losses, the doctrine of piercing the corporate veil becomes applicable to impose personal liability. In Decision Number 477/Pdt.G/2018/PN.Jkt.Sel, the commissioner was found to have committed an unlawful act under Article 1365 of the Civil Code and held personally liable pursuant to Article 114 paragraph (3) of the Company Law.